Diversity management in India: A study of organizations in different ownership forms and industrial sectors - Cooke, Fang Lee; Saini, Debi S. (Human Resource Management, 2010)
AbstractStrategically managing workforce diversity is a value‐adding HR function that enhances organizational performance. Managing diversity is a complex and unique HR issue in India due to its religious and cultural diversity and the use of legislation by the Indian state to tackle societal inequities and complexities. This paper contributes to existing knowledge on diversity management and strategic HRM in the Indian context through an in‐depth case study of 24 firms of different ownership forms in a number of industries in India. The main method of data collection was semi‐structured interviews with 110 managers at various levels and 102 non‐managerial employees. Each interview was conducted individually. This paper takes the U.S.‐originated concept of diversity management in the HRM context as a starting point. It uses this as a guide to investigate how the concept is understood and operationalized in several leading business organizations across different ownership forms and industrial sectors in India. Results reveal the differences between Western MNCs and Eastern firms as well as the varying views of Indian managers and employees on issues related to diversity management. © 2010 Wiley Periodicals, Inc.